2012
DOI: 10.1002/pc.22381
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy/anhydride networks modified with polyhedral oligomeric silsesquioxanes

Abstract: Epoxy/anhydride networks were modified, in the presence of benzyldimethylamine as catalyst, with two polyhedral oligomeric silsesquioxanes (POSS), whose inorganic framework had a compact and stable Si‐O core and an organic substituent shell. The influence of the content and type of POSS during curing and on the properties of the thermosets was investigated by thermal analysis and infrared spectroscopy. The curing kinetics was analyzed by means of an integral isoconversional nonisothermal procedure. When the PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Table 2 shows the experimental heats of polymerization, Dh, calculated as the average heat of the experiments at different heating rates. By increasing the proportion of modifier Dh (J=g) decreases due to the lower content of reactive epoxy and anhydride groups, whereas Dh (kJ=ee) remains almost constant and similar to the values reported in the literature [19,[26][27][28] . FTIR spectra of cured samples showed that the absorbance bands at 913 cm À1 and at 1860-1780 cm À1 (figure not shown), attributed to the oxirane and anhydride groups, respectively, disappeared completely.…”
Section: Results and Discussion Curing Of Dgeba/mthpa With Different supporting
confidence: 87%
“…Table 2 shows the experimental heats of polymerization, Dh, calculated as the average heat of the experiments at different heating rates. By increasing the proportion of modifier Dh (J=g) decreases due to the lower content of reactive epoxy and anhydride groups, whereas Dh (kJ=ee) remains almost constant and similar to the values reported in the literature [19,[26][27][28] . FTIR spectra of cured samples showed that the absorbance bands at 913 cm À1 and at 1860-1780 cm À1 (figure not shown), attributed to the oxirane and anhydride groups, respectively, disappeared completely.…”
Section: Results and Discussion Curing Of Dgeba/mthpa With Different supporting
confidence: 87%
“…This can be achieved by incorporating structural features that enhance flexibility or mobility within the backbone of the polymer while potentially minimizing deleterious impact upon other properties. Examples of this include increasing the molecular weight between crosslinks, blending epoxy resins with different structure, or incorporating greater aliphatic rather than aromatic groups into a network …”
Section: Introductionmentioning
confidence: 99%
“…Also, their structures which are prone to brittle (Ersoy, 2001), combustible and fragile, restrict the use of such resins (Güzel, 2016). Hardened resin layer's physical and mechanical properties depend on the functional group types of hardener, cross-link density between resin and hardener, molecular structure and hardening conditions of functional group bonds between resin and hardener (Şahmetlioğlu, 2000;Nohales et al, 2006;Montero et al, 2013;Güzel, 2016).…”
Section: Resultsmentioning
confidence: 99%